Women Teachers, Essays and Civic Writing in “Repertorio Americano” - Soto Ramírez, Marybel (Revista Electrónica Educare, 2011)
Women writing, as any symbolic form of production, has existed and developed despite of the patriarchal imperative commanding women to obey and to remain silent. It is not the objective of this essay to deepen on the deeds and doings of those women who, throughout history and despite patriarchal mandates, have exerted their writing as a transgression as a way to show and to affirm themselves before others. Moreover, my purpose is to identify women in Repertorio Americano (1919-1958) who as teachers and writers elaborated civic discourses and questioned the very meaning of patriotism and civic feelings in the constructions of a citizenship they were not fully and formally entitled to.